2018
DOI: 10.1021/acs.bioconjchem.8b00004
|View full text |Cite
|
Sign up to set email alerts
|

Ferritin Nanocages with Biologically Orthogonal Conjugation for Vascular Targeting and Imaging

Abstract: Genetic incorporation of biologically orthogonal functional groups into macromolecules has the potential to yield efficient, controlled, reproducible, site-specific conjugation of affinity ligands, contrast agents, or therapeutic cargoes. Here, we applied this approach to ferritin, a ubiquitous iron-storage protein that self-assembles into multimeric nanocages with remarkable stability, size uniformity (12 nm), and endogenous capacity for loading and transport of a variety of inorganic and organic cargoes. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 70 publications
0
34
0
Order By: Relevance
“…Therefore, both Ab/(Ft/SOD) and (Ab + SOD)/Ft displayed similar size characteristics of 20–25 nm in diameter with PDI 0.20–0.24. Earlier we have demonstrated that on average three molecules of IgG can be conjugated to the surface of Ft particle under the described conditions [40]. Therefore, one Ab/(Ft/SOD) particle contains on average 3 and 2 molecules of IgG and SOD, respectively.…”
Section: Resultsmentioning
confidence: 82%
“…Therefore, both Ab/(Ft/SOD) and (Ab + SOD)/Ft displayed similar size characteristics of 20–25 nm in diameter with PDI 0.20–0.24. Earlier we have demonstrated that on average three molecules of IgG can be conjugated to the surface of Ft particle under the described conditions [40]. Therefore, one Ab/(Ft/SOD) particle contains on average 3 and 2 molecules of IgG and SOD, respectively.…”
Section: Resultsmentioning
confidence: 82%
“…Consequently, interest in application of ferritin nanocage in drug delivery and MRI imaging has been increasing. [12,[37][38][39][40][41][42] Yet, its use for making antiviral mosaic nanocages to target viral particles has not been demonstrated. I will discuss four strategies to engineer ferritin and create antiviral mosaic nanocages as therapeutic candidates with the aim to address the current global pandemic of SARS-CoV-2.…”
Section: Ferritin Structure and Functionmentioning
confidence: 99%
“…[48] On the other hand, protein nanocages and ferritins furnished with multiple copy of a single antibody have been described for targeting specific cells and drug delivery. [39,40,49,50] However, mosaic nanocages to deliver a cocktail of antibodies and treat viral infections have yet to be described. These nanocages could significantly improve the efficacy of antibody therapy by preventing the emergence of scape variants and the ADE of infection.…”
Section: Mosaic Nanocages For Antibody Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…To increase targeted ferritin delivery, more selective ligands of cell surface markers, such as peptides and antibodies, have been conjugated to the external surface of ferritin [25]. In this contest, Khoshnejad M. et al have shown high pulmonary endothelial targeting in vivo, with no noticeable undesired effects, by functionalizing ferritin with antibodies specific for ICAM-1 [26]. The present review aims to highlight recent advances achieved using both H-and L-ferritins, loaded with paramagnetic metals or complexes, as highly sensitive MRI probes ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%